A comparison of harmonic and traditional sharp staphylectomy techniques in 15 brachycephalic dogs. (30th September 2022) - Gilman, O.; Moreira, L.; Dobromylskyj, M.; Doran, I.
Abstract : Objectives: The objective was to compare sharp staphylectomy and staphylectomy using harmonic focus shears, assess surgical time, intraoperative haemorrhage and outcome. Our hypothesis was that harmonic staphylectomy would result in reduced surgical time, decreased intraoperative haemorrhage and greater relative improvement. Materials and Methods: Dogs that were presented to Highcroft Veterinary Referrals between July 2020 and September 2021 with brachycephalic obstructive airway syndrome and underwent surgical correction were prospectively enrolled. Surgical technique was randomised, and surgical time, staphylectomy time, intraoperative haemorrhage, hospitalisation and change in patients' Cambridge BOAS Grade at a 14‐day recheck were recorded. Results: Fifteen dogs were enrolled: seven dogs underwent sharp and eight underwent harmonic staphylectomy. Nine patients returned for follow‐up, four of seven and five of eight, respectively. Harmonic staphylectomy was associated with less haemorrhage (0 versus 9 cotton buds) and a shorter average staphylectomy time (3 minutes 36 seconds versus 14 minutes 50 seconds). No statistically significant differences were observed in total surgery time, number of nights hospitalised, or change in Cambridge BOAS Grade. An average of 0.68 mm of thermal necrosis was seen at the cut edges of soft palates removed by harmonic staphylectomy. Clinical Significance: Harmonic staphylectomy can result in a reduction in staphylectomy time and degree of intraoperative haemorrhage compared to sharp staphylectomy, with no deleterious impact on postoperative recovery or the long‐term outcome of patients.